Brand: Image of recognition of entrepreneurial synergy - Mircea Alecsandru Udrescu; Andrei Buiga (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
Brand represents reputation of offer. Branding means cultivating the reputation of offer. But brand and branding are synergistic actions of entrepreneurship, a combination of vision and promotion strategy of offer by the management team. Brand is a reputation of something as a result of the actions taken by someone interested. Many beautiful places of nature exist in different parts of the world, but also in the tourists minds, because their beauty and perfection is always maintained by the unequaled creator: nature itself. Likewise, in society, products and services become brands, as far as the one who produces aims to achieve the highest level of customer satisfaction through quality of supply. That is why, the reputation originates from fulfilled pleasure. And such a state is felt only if the entrepreneur creates unique value for the customer and make things better than the competition. This is how social success is built up. We believe that the country brand is the way in which Romanians travel around the world and how they treat their guests. A country brand can't be built up with a leaf and a marketing campaign, although it is a tourism brand, but money, that could have been used for a better purpose, were certainly spent in a lamentable way.
Keywords: 330; brand; branding; product; mark features; quality; needs; desires; requirements; competitiveness; satisfaction; pleasure